A False Bank Accounts Detection Method Based on Naive Bayesian Network. Issue 1 (March 2021) - Wan, Weiqing; Li, Weihong
Abstract: At present, more and more cases of economic fraud are based on false bank accounts. Due to the limitation of the bank's technology and ability to verify the true identity of customers, the online verification system of banks can only check the authenticity of the ID card, while the consistent verification of people and cards can only be completed manually by bank tellers. It is easy to produce errors if the consistency is judged by the teller's manual naked eye. In this paper was proposed a method of constructing a naive Bayesian network classification model by automatically detect the authenticity of bank accounts to avoid the problem of economic fraud of false bank accounts, and verified the feasibility of this method through specific examples. The experimental results show that the method which has certain theoretical and practical significance, and provides reference for the detection of other false accounts.